NOx emissions and the component changes of ternary molten nitrate salts in thermal energy storage process. (15th December 2016) - Yang, Chuntao; Wei, Xiaolan; Wang, Weilong; Lin, Zihao; Ding, Jing; Wang, Yan; Peng, Qiang; Yang, Jianping
Highlights: NOx emissions from ternary molten nitrate salts in used temperature were investigated. The effect of 45 # carbon steel on NOx emissions was studied. Chemical thermodynamic calculations of related reactions for NOx production were carried out. NOx emissions increased with the rise of the temperature. Abstract: The objective of this work is to investigate the NO x emissions from HITEC (ternary molten nitrates of 7 wt.%NaNO3 -53 wt.%KNO3 -40 wt.%NaNO2 ) in thermal energy storage (TES) process and the effects of 45 # carbon steel (1045, ASTM) on NO x emission as well as the component changes in HITEC. Referring to the national environmental protection standard (HJ479-2009) in China, NO x emissions in tail gases were measured in one hour for heating the molten salts in a quartz glass boat during TES process. Furthermore, the concentrations of nitrate and nitrite ion in molten salts samples were determined, and chemical thermodynamic calculations of related reactions were carried out to explain the mechanism of NO x emissions. The results show that HITEC contained in a quartz glass or carbon steel container in air atmosphere can release NO x in the operating temperature range, which were caused by several reactions between nitrate and SiO2 or Fe. The concentrations of NO x emissions increase with the rise of temperature. In the practical application, NO x emission is acceptable since the amount of NO2 or NO will dramatically decreased in the liquid salts by reacting with NaNO2 .